2021
DOI: 10.1021/acs.jpcc.1c09281
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Optical Properties of CH3NH3PbBr3 Single Crystals across the Structural Phase Transitions by Spectroscopic Ellipsometry

Abstract: Lead halide perovskites have drawn considerable attention on account of their potential applications in solar cell and optoelectronic devices. To realize such technological possibilities, the optical characterizations of these materials must be assessed. This paper presents a comprehensive study of the temperaturedependent optical properties of CH 3 NH 3 PbBr 3 single crystals between 4.5 and 400 K within an energy range of 0.73 to 6.42 eV determined through spectroscopic ellipsometry. The profile of the room-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The XRD patterns of MAPbBr 3 films grown on blank substrates and ITO buffer layers with different precursor concentrations are shown in Figure b. Similar peaks were also reported in other studies. , The diffraction peaks at 14.85, 21.15, 25.95, 30.10, 33.75, 45.85, 53.23, and 63.4° (2θ) corresponded with (100), (110), (111), (200), (210), (300), (222), and (400) crystal planes, respectively. The characteristic peaks of the ITO were visible in MAPbBr 3 /ITO, as shown in Figure S2 in the Supporting Information.…”
Section: Results and Discussionmentioning
confidence: 95%
“…The XRD patterns of MAPbBr 3 films grown on blank substrates and ITO buffer layers with different precursor concentrations are shown in Figure b. Similar peaks were also reported in other studies. , The diffraction peaks at 14.85, 21.15, 25.95, 30.10, 33.75, 45.85, 53.23, and 63.4° (2θ) corresponded with (100), (110), (111), (200), (210), (300), (222), and (400) crystal planes, respectively. The characteristic peaks of the ITO were visible in MAPbBr 3 /ITO, as shown in Figure S2 in the Supporting Information.…”
Section: Results and Discussionmentioning
confidence: 95%
“…43 The diffraction peaks at 14.85, 21.15, 25.95, 30.10, 33.75, 45.85, 53.23, and 63.4°(2θ) correspond to the (100), ( 110), ( 111), ( 200), ( 210), (300), (222), and (400) crystal planes, respectively. 44,45 Studies have indicated that both the substrate material and the thickness of the spin-coated perovskite layer can affect the crystalline quality of the perovskite. 46 According to Bragg's law, specific interplanar spacing (d) will result in intense diffraction peaks at specific angles (θ).…”
Section: Resultsmentioning
confidence: 99%
“…8 The listed approaches were used to determine the optical constants of the most studied iodide perovskite MAPbI 3 1,2,4,5,7,8 and mixed-cation (MA,FA)PbI 3 , 11 bromide perovskites CsPbBr 3 , 6,12,13 MAPbBr 3 12−14 and FAPbBr 3 , 12,13 and chloride perovskite MAPbCl 3 . 9 Most of the above-mentioned studies were performed at room temperature or in its close vicinity, with the exception of cryogenic studies from 4 K for MAPbBr 3 14 and (MA,FA)-PbI 3 11 and from 77 K for MAPbI 3 . 4 Direct measurement of the refractive index in semiconductors is possible by observation of the interference of light reflected from the front and back surfaces of the crystal (Fabry−Perot interference).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thin perovskite films may have a surface of fairly high optical quality, but results of optical measurements will greatly depend on the film manufacturing method, the size, and orientation of its constituent grains. In a number of works, ellipsometry has been applied to perovskite single crystals. Alternative methods for determining the optical constants of perovskites are simultaneous reflection and transmission measurements , and Brewster angle measurements from polished or natural facets of single crystals . The listed approaches were used to determine the optical constants of the most studied iodide perovskite MAPbI 3 ,,,,, and mixed-cation (MA,FA)­PbI 3 , bromide perovskites CsPbBr 3 , ,, MAPbBr 3 and FAPbBr 3 , , and chloride perovskite MAPbCl 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation